Load frequency controller design based on extreme learning machine (ELM) - Tangka, Yossy. (2009)
In this project the multi area power plant system and its dynamics are studied. Furthermore the modeling of the three-area power plant using SIMULINK and simulation of the system using a decentralized robust controller when subjected to system parameter uncertainties and the unpredictable change of load. Simulation results show that the decentralized load frequency controller can ensure that the system is stable for all bounded parametric uncertainties, even in the presence of generation rate constraint. Other controller design technique using extreme learning machine (ELM) is proposed and evaluated for its performance when subjected to uncertainties of the system’s parameters and different load change.